2023
DOI: 10.1126/science.adf3974
|View full text |Cite
|
Sign up to set email alerts
|

Engineered bacteria detect tumor DNA

Abstract: Synthetic biology has developed sophisticated cellular biosensors to detect and respond to human disease. However, biosensors have not yet been engineered to detect specific extracellular DNA sequences and mutations. Here, we engineered naturally competent Acinetobacter baylyi to detect donor DNA from the genomes of colorectal cancer (CRC) cells, organoids, and tumors. We characterized the functionality of the biosensors in vitro with coculture assays and then validated them in vivo wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Further study demonstrated that the analytical performance of the technology is equivalent to that obtained after purification and concentration, with a precision of ∼1% for size features ( Boutonnet et al, 2023 ). In addition, several emerging technologies, including sophisticated cellular biosensors ( Cooper et al, 2023 ), electrochemical biosensors ( Wang et al, 2022 ) and fluorescence-enhancing all-dielectric metasurface biosensors ( Iwanaga et al, 2023 ), can detect the content of cfDNA without complicated processing. These methods with high sensitivity have advantages in low-content detection, but they are not suitable for more detailed analysis of DNA fragments, so they are not generally used for quality control of cfDNA analysis.…”
Section: Preanalytical Variables Affecting Cfdna Analysismentioning
confidence: 99%
“…Further study demonstrated that the analytical performance of the technology is equivalent to that obtained after purification and concentration, with a precision of ∼1% for size features ( Boutonnet et al, 2023 ). In addition, several emerging technologies, including sophisticated cellular biosensors ( Cooper et al, 2023 ), electrochemical biosensors ( Wang et al, 2022 ) and fluorescence-enhancing all-dielectric metasurface biosensors ( Iwanaga et al, 2023 ), can detect the content of cfDNA without complicated processing. These methods with high sensitivity have advantages in low-content detection, but they are not suitable for more detailed analysis of DNA fragments, so they are not generally used for quality control of cfDNA analysis.…”
Section: Preanalytical Variables Affecting Cfdna Analysismentioning
confidence: 99%
“…Bacteria also naturally colonize tumors [13]. That in combination with the uptake of cell-free DNA via a competence mechanism could possibly help enable multiregion, multisample tumor sequencing [14].…”
Section: Bacterial Competencementioning
confidence: 99%
“…Bacteria also naturally colonize tumors [11]. That in combination with the uptake of cell-free DNA via a competence mechanism could possibly help enable multiregion, multisample tumor sequencing [12].…”
Section: Bacterial Competencementioning
confidence: 99%